2018
DOI: 10.1055/s-0038-1675345
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of the Lymph Node Factor in Surgically Resected Non-Small Cell Lung Cancer

Abstract: Background Patients with N1 non-small cell lung cancer represent a heterogeneous population. The aim of this study is to determine the difference of survival rate between subtypes of N1 disease in surgically resected non-small cell lung cancer patients and to compare the survival in these patients with multi-N1 and single N2 (skip metastasis) disease. Methods Patients who underwent anatomical pulmonary resection in our institution between 2007 and 2014 with a pathological diagnosis of N1 and single N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition, several studies showed 5-year overall survival rates in patients with occult single-level N2 disease treated with curative-intent resection and adjuvant chemoradiotherapy that were comparable to those in patients with N1 disease. 55,56 The extensiveness of N2 nodal metastasis, however, remains important because significant differences in overall survival were found between patients with single-and multiple-station N2 disease and between patients with microscopic (0.2-2 mm) and macroscopic N2 disease. 57,58 In the ASTER trial, mediastinoscopy-diagnosed N2/N3 disease after negative endosonography findings was found in 9.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies showed 5-year overall survival rates in patients with occult single-level N2 disease treated with curative-intent resection and adjuvant chemoradiotherapy that were comparable to those in patients with N1 disease. 55,56 The extensiveness of N2 nodal metastasis, however, remains important because significant differences in overall survival were found between patients with single-and multiple-station N2 disease and between patients with microscopic (0.2-2 mm) and macroscopic N2 disease. 57,58 In the ASTER trial, mediastinoscopy-diagnosed N2/N3 disease after negative endosonography findings was found in 9.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate analysis revealed that port was an independent predictive factor for adverse os (hr: 2.618; 95% ci: 1.185 to 5.785; p = 0.017). Numerous studies have proposed that the prognosis for patients with nsclc having single-station skip mediastinal ln metastasis (N2a1) is close to that for patients with pN1 disease 14,24,25 . Thus, it could be speculated that nsclc at the N2a1 pathologic stage might exhibit biologic behaviours similar to those at the N1 stage.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that lymph node metastases are seeded a long before clinical detection and, at that moment, they do not contribute to migration to other sites; however, they evolve in parallel with primary tumors sharping the genetic divergence [ 116 , 122 ]. Primary NSCLC, and its corresponding lymph node metastases, present high concordance in clonal alterations, indicating that local metastases may arise from the major clone of primary tumor [ 114 , 123 ]. Moreover, the NPIPA1 gene mutation and NKX2/1 gene amplification are evident drivers of lymph nodes metastases [ 116 ].…”
Section: Clonality Of Metastasesmentioning
confidence: 99%
“…Due to a common ancestor, primary NSCLC and its lymph node metastases should be susceptible to the same treatment regimen. However, the genetic heterogeneity between both lesions seems to be the main reason for recurrence after surgical resection [ 123 , 124 ]. Lymph nodes metastases may be considered a reservoir for distant spreading of NSCLC; however, distant metastases that were seeded from the primary tumor or metastatic lymph nodes indicated divergent evolutionary trajectories [ 114 , 116 , 125 ].…”
Section: Clonality Of Metastasesmentioning
confidence: 99%